Explaining the Frequency and Variety of Crimes through the Interaction of Individual and Contextual Risk Factors - Parent, Geneviève (Canadian journal of criminology and criminal justice, 2016)
This study explored the explanatory power of the interaction model between individual and contextual risk, in comparison to the additive model, to explain delinquency. It was conducted with 235 offenders, who completed self-report questionnaires regarding antisocial traits and attitudes, criminal entourage, lifestyle, and delinquency. Multiple linear regression analyses (additive combination) and regression trees (interaction combination) were produced. In general, the factors favouring the formation of criminogenic situations (personal characteristics, criminal entourage, and deviant lifestyle) all significantly contributed to the explanation of the frequency and variety of crimes. However, the regression tree results suggested that it is necessary to understand the level of both individual and contextual risk to adequately explain delinquency. Our results suggest abandoning the additive approach currently used in the assessment of recidivism risk in favour of an interactional approach because it better reflects reality.